Community Assistance Through The Cyclone Ventilator Modification (CVM) Application In Reducing Cases Of Tuberculosis Transmission At The Pegirian Health Center In Surabaya City In 2024 Rach - Rachmaniyah (Frontiers in Community Service and Empowerment, 2026)
The risk of TB transmission in families needs to be paid attention to, especially in toddlers and the elderly who have lower immunity. The TB death rate in East Java is still high, including the city of Surabaya. In preventing TB transmission, the role of the family is very important, because one of the tasks of the family is to provide care for sick family members and prevent transmission to healthy family members through efforts that must be applied in their daily lives. Efforts to prevent the transmission of diseases, especially tuberculosis, can be done by improving the air quality in patients' homes and sanitation facilities so as to support the realization of healthy homes. A healthy house is a house with physical facilities that meet the requirements for the health of its occupants such as the fulfillment of ventilation, lighting, humidity, residential density, which as a whole must meet the requirements according to the standards of the Ministry of Health No.829 of 1999 so that the house does not become a medium for disease transmission. The purpose of community service is to increase public knowledge about environment-based infectious diseases including TBC, PHBS, CTPS diseases, improve the air quality of patients' home rooms by installing Cyclone Ventilator Modification (CVM) in an effort to prevent the transmission of tuberculosis in the work area of the Pegirian Health Center in Surabaya in 2024. The target of the activity is aimed specifically at residents with tuberculosis in the Working Area of the Pegirian Health Center, Surabaya City. The approach is carried out by observation, interviews, counseling, demonstrations of the installation of CVM devices in the homes of TB patients, motivating residents in realizing healthy homes and environments by providing assistance in the form of CVM devices, CTPS souvenrs